Fisheries guidelines in the conduct of yield of trials of fisheries technology and for the assessment - Fortes, R.D., Fortes, N,R. and Pagbilao, C.R. (Diliman, Quezon City Department of Agriculture, Bureau of Agricultural Research, 1991)
Farm Research Manual Module 8
Keywords: Agriculture-Research--On-farm.; Agricultural systems--Handbooks, manuals, etc; Fisheries--Handbooks, manuals, etc; Fishery Technology